The Effect of Assistant Media on Block Ability Field Tennis Game - Muhammad Ali; Fajar Vidya Hartono; Abdul Sukur; Ahmad Atiq; Choirul Umam; Andika Andika; Sumajaya Sumajaya; Agus Setiawan (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2022)
This study aims to determine the effect of auxiliary media on the hitting ability of the tennis game. The research method used is an experimental method, namely using a pre-experimental design experimental design. For a more specific experimental research design, the author uses a one-group pretest-posttest research model. The population in this study were third-grade students of SD Negeri 1 Jambi which consisted of 1 class totalling 31 students. The sample in this study were all third-grade students at the 1jambi State Elementary School, totalling 31 students who were designated as all samples because the number of samples or subjects was less than 100 people, therefore the sampling used the total sampling technique, which included all members of the population as research sample. Based on the results of the research, the count value is 5,208 by looking at the statistical table where the degrees of freedom db=(N-1) are 31-1=30 and at the 5% significance level, the t-table value is 2,042. Thus, it can be concluded that the value of t-test > t-table or 14,667 > 2,042, meaning that the hypothesis is accepted that there is an effect of using auxiliary media on the ability to play tennis in third-grade students of SD Negeri 1 Jambi. The percentage increase is 34.9%.